Development of an indexed score to identify the most suitable sampling method to assess occupational exposure to fungi - Cervantes, Renata (2022)
The sampling approach is of utmost importance to obtain data regarding microbial viability and truly assess workers’ potential health effects. The purpose of this assessment is to create a score that will provide up-to-date information to identify the most suitable sampling method to assess occupational exposure to fungi. Data from a sampling campaign performed at Firefighters Headquarters (FFH) was analyzed and a score was calculated from one (1) to three (3) for five (5) distinct sample parameters: (a) accuracy; (b) complexity of the fieldwork; (c) cost; (d) complexity in laboratory work; and (e) time is taken since the fieldwork until obtaining the fungal contamination characterization. The statistical analysis allowed us to conclude that settled dust and Andersen's six-stage were the best sampling methods to perform the assessment of the occupational exposure to fungi at FFH when considering the number of species. As for the final score, the results showed that surface swabs were the best sampling method. The results obtained for surface swabs highlight the low complexity of this processing combined with the fact that it is a low-cost sampling method. This study reinforces the need to use a wide array of sampling methods when assessing occupational exposure to fungal contamination to ensure an accurate risk characterization.